CHALLENGES FACED BY SIGN LANGUAGE INTERPRETERS IN CLASSROOM: A CASE STUDY OF PSL LEARNERS BY USING MAXQDA (Al-Aasar, 2025)
This study highlights the challenges faced by sign language interpreters while handling hearing impaired Pakistan Sign Language learners in classroom. Sign language interpreters facilitate the communication between hearing impaired individuals and course instructors in classroom. According to Linguistic Society of America (2002), It is highly required for interpreters to have linguistic experience as well as certain knowledge of content they are interpreting. It also emphasizes that they have enough time to analyze handouts before meeting hearing impaired students. They need to pay close attention to conveying meaning while taking into account both linguistic and cultural variations (Ackroyod & Wright,2018). They need to be professionally trained in adjusting their interpreting style to meet the individual needs of each student and they must have knowledge of social, cultural and linguistic nuances in this context (Hameed & Sulman, 2023). This study incorporates qualitative case study design while using MAXQDA. MAXQDA as a tool is used to analyze data collected from observations and interviews of sign language interpreters. Findings suggest that interpreters face challenges of emotional and cultural sensitivity, complex academic content as they are not subject specialists. The presence of different varieties of PSL in classroom is the main difficulty for interpreters while facilitating effective communication between hearing impaired PSL learners and course instructors. Thoutenhoofd (2005) argued that The Policy of educational inclusion and Language of curriculum turn out to be  a huge barrier for  interpreters. This study is benefited in dual dimensions, that is sign language interpreters and hearing-impaired Pakistan Sign Language learners at graduate level. It confirms that interpreters adapt different strategies for ensuring effective quality of education for PSL learners from different areas of Pakistan in classroom.